Determination of the Relationship Between Kobayashi, Sano, and Egami Criteria and Prevalence of Intravenous Immunoglobulin Resistance and Coronary Artery Aneurysm in Iranian Children with Kawasaki Disease - Shashaani N (Dove Medical Press, 2020)
Niloufar Shashaani,1 Reza Shiari,2 Abdullah Karimi,3 Shima Salehi,4 Roxana Ghanaei,3 Mehrnoush Hassas Yeganeh,2 Sara Shiari,1 Khosro Rahmani,2 Vadood Javadi Parvaneh2 1Faculty of Medicine, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 2Department of Pediatric Rheumatology, Mofid Children’s Hospital, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 3Department of Infectious Diseases, Mofid Children’s Hospital, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 4Faculty of Medicine, Ali Asghar Children’s Hospital, Iran University of Medical Sciences, Tehran, IranCorrespondence: Reza Shiari Tel +98-21-22227033Email shiareza@yahoo.comIntroduction: Kawasaki disease (KD) is a systemic vasculitis that occurs mostly in children under five years old. Kawasaki affects the middle-size arteries, especially the coronary arteries. Therefore, without adequate treatment, it may cause coronary artery aneurysm in 25% of patients. The purpose of this study was to investigate the relationship between Kobayashi, Sano, and Egami criterions with coronary artery aneurysm in KD patients during the last ten years and to identify risk factors in patients with intravenous immunoglobulin (IVIG)-resistant and coronary artery aneurysms.Methodology: Medical records of 363 Kawasaki patients referred during 2008– 2017 were reviewed. Patients’ demographic data and Kobayashi, Sano, and Egami scores of each patient were calculated. Based on echocardiographic findings, cases of coronary artery aneurysm were determined. Sensitivity, specificity, positive and negative predictive value, and the accuracy of each criterion were determined to predicting IVIG resistance and detect coronary artery aneurysm.Results: There was a slight relationship between IVIG-resistance in Kawasaki children and its prediction based on the Kobayashi risk score, but no relationship was found between the Egami and Sano criteria. Sixty-three patients (17.4%) had coronary artery lesions (CALs) on time of diagnosis. There were no statistically significant differences between gender and mean age of children with and without CALs. Also, there was no significant relationship between coronary artery aneurysm in Kawasaki children and its prediction based on the above three risk factors. The area under the ROC-curve of all three risk measures of Kobayashi, Egami, and Sano indicated that all three criteria were not useful in predicting CALs.Conclusion: Despite the low accuracy of the three above criteria to predictive of patients with IVIG resistance, it seems that the variables of age, duration of fever, and C-reactive protein (CRP) are more useful than other variables and may be utilized to evaluate patients by establishing a more appropriate cut-off point.Keywords: Kawasaki disease, coronary artery aneurysm, IVIG-resistant, Kobayashi, Sano, Egami